Optimization of fermentation conditions for 2,3-butanediol production from Helianthus tuberosus hydrolysate by Raoultella ornithinolytica - LI Feng, YANG Lin, XIE Guoyou, XU Ping (Zhongguo niangzao)
2,3-butanediol was produced by Raoultella ornithinolytica TH-21 using Helianthus tuberosus hydrolysate as raw material. Fermentation temperature, time, rotation rate and yeast extract mass concentration were selected as the influencing factors, the effects of each single factor on the 2,3-butanediol production were investigated, and the fermentation conditions were optimized by response surface tests. The results showed that the optimal fermentation conditions were as follows: fermentation temperature 28 ℃, fermentation time 25 h, rotation rate 270 r/min and yeast extract mass concentration 12 g/L. Under these optimal conditions, the 2,3-butanediol production could reach 19.2 g/L, which was increased by 22.68% compared to that before optimization. When the fermentation time was 25 h, the mass concentration of reducing sugar was 3.75 g/L, and the mass concentration of 2,3-butanediol was the highest (19.2 g/L), indicating that the R. ornithinolytica TH-21 metabolized the carbohydrates to produce 2,3-butanediol within the initial 25 h.